2015
DOI: 10.1007/s10935-015-0405-4
|View full text |Cite
|
Sign up to set email alerts
|

Universal Prevention for Anxiety and Depressive Symptoms in Children: A Meta-analysis of Randomized and Cluster-Randomized Trials

Abstract: Although under-diagnosed, anxiety and depression are among the most prevalent psychiatric disorders in children and adolescents, leading to severe impairment, increased risk of future psychiatric problems, and a high economic burden to society. Universal prevention may be a potent way to address these widespread problems. There are several benefits to universal relative to targeted interventions because there is limited knowledge as to how to screen for anxiety and depression in the general population. Earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 78 publications
8
69
0
1
Order By: Relevance
“…The effect sizes we obtained (e.g., .12 for component worries and .09 for internalising difficulties ) are comparable to those reported for other similar interventions in a recent meta‐analysis of universal preventive interventions (e.g., Cohen's d of .13 in Ahlen, Lenhard, & Ghaderi, ) and the effects persisted at the 6‐month follow‐up (e.g., Cohen's d of .11 in Ahlen et al, ). Effect sizes should be interpreted in the light of prevention science, for example, in educational research, an effect size of .20 is regarded as sufficient to warrant a change in policy (Hedges & Hedberg, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The effect sizes we obtained (e.g., .12 for component worries and .09 for internalising difficulties ) are comparable to those reported for other similar interventions in a recent meta‐analysis of universal preventive interventions (e.g., Cohen's d of .13 in Ahlen, Lenhard, & Ghaderi, ) and the effects persisted at the 6‐month follow‐up (e.g., Cohen's d of .11 in Ahlen et al, ). Effect sizes should be interpreted in the light of prevention science, for example, in educational research, an effect size of .20 is regarded as sufficient to warrant a change in policy (Hedges & Hedberg, ).…”
Section: Discussionsupporting
confidence: 84%
“…Greenberg, Domitrovich, and Bumbarger () noted that as well as reducing anxiety, there is a strong probability that cognitive behavioural programs also have a beneficial impact on related difficulties (e.g., externalisation difficulties), and we would also like to test this probability. In a study similar to ours, Ahlen et al () found that the effects of an intervention were not moderated by any of the following preselected variables: the primary target of the intervention (anxiety or depression), the deliverer of the intervention, sex distribution of the group, age of participants or length of the intervention. In future research, we hope to include analyses of potential moderator variables (e.g., personality traits, group size) and to compare the online delivery of the program with conventional, group‐based face‐to‐face delivery.…”
Section: Discussionsupporting
confidence: 58%
“…To date, the bulk of prevention research has universally targeted a broad array of anxiety symptoms in children and early adolescents (e.g., the FRIENDS Program; Barrett, Farrell, Ollendick, & Dadds, 2006; Essau, Conradt, Sasagawa, & Ollendick, 2012), with meta-analytic findings supporting only modest improvements in anxiety-specific symptoms following universal prevention at post-test and follow-up (Ahlen, Lenhard, & Ghaderi, 2015). In contrast, social anxiety-specific research has focused almost exclusively on treating clinical levels of SAD using behavioral and cognitive-behavioral treatment models (e.g., Beidel, Turner, & Morris, 2000; Masia Warner et al, 2005), including treatment studies conducted within school settings (Masia Warner, Colognori, Brice, & Sanchez, 2015).…”
Section: Prevention Of Social Anxiety and Depressionmentioning
confidence: 99%
“…Nonetheless, the research evidence to date has not clarified if it is more effective to target entire populations (so-called “universal” interventions) (1417), or whether it is more effective to identify and then intervene in a smaller “high-risk” group (1821). Overall, research findings and reviews have been supportive of a variety of both high-risk and universal interventions potentially reducing suicide rates in those aged 11–18, without definitively determining if one approach has better outcomes (2227).…”
Section: Introductionmentioning
confidence: 99%